2018
DOI: 10.1016/j.ajic.2018.04.222
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the effect of preparation for and participation in a hand-sanitizing relay on nursing students' ability to recall the WHO 6-step hand hygiene technique

Abstract: This study explored whether preparation for a hand-sanitizing relay affected nursing students' ability to recall, 12 months later, the World Health Organization 6-step hand hygiene technique. No significant difference was observed in recall between those who participated in the relay and those who did not (P = .736). The most frequently missed step was Step 3 (palm to palm with fingers interlaced). Our results suggest that regular feedback may be an important additional component in future interventions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 8 publications
0
11
0
Order By: Relevance
“…Other literature also shows the effectiveness of HH education devices and tools. 33,[39][40][41][42] In this study, the HH compliance rate was 52.2% in the experimental group and 39.1% in the control group. Observational studies have examined HH compliance rates of health care workers and found that compliance scores vary between 40% and 78%.…”
Section: Discussionmentioning
confidence: 52%
See 1 more Smart Citation
“…Other literature also shows the effectiveness of HH education devices and tools. 33,[39][40][41][42] In this study, the HH compliance rate was 52.2% in the experimental group and 39.1% in the control group. Observational studies have examined HH compliance rates of health care workers and found that compliance scores vary between 40% and 78%.…”
Section: Discussionmentioning
confidence: 52%
“…Thus, the students improved their HH skills by repeating the process until they fully implemented HH. Other literature also shows the effectiveness of HH education devices and tools 33,39–42…”
Section: Discussionmentioning
confidence: 99%
“…The 12 studies included in this systematic review were published between 2003 and 2021 and originated from eight countries: Jordan ( n = 3), China ( n = 2), United Kingdom ( n = 2), India ( n = 1), Iran ( n = 1), South Korea ( n = 1), Singapore ( n = 1), and the United States ( n = 1). Six studies were RCTs (Al-Hussami & Darawad, 2013; Bloomfield et al, 2010; Konicki & Miller, 2016; Sadafi et al, 2021; Wang et al, 2003; Xiong et al, 2017); three studies were two-group quasi-experimental in design (Kim et al, 2021; Price et al, 2018; Tawalbeh et al, 2019); three were one-group quasi-experimental studies (Hassan, 2018; Mathai et al, 2011; Salmon et al, 2013).…”
Section: Resultsmentioning
confidence: 99%
“…The length of the nursing program and academic year in which the study was conducted varied across countries. Students were recruited in their first year ( n = 1; Bloomfield et al, 2010), second year ( n = 3; Konicki & Miller, 2016; Price et al, 2018; Sadafi et al, 2021), third year ( n = 3; Kim et al, 2021; Salmon et al, 2013; Tawalbeh et al, 2019), fourth year ( n = 1; Wang et al, 2003), and postdidactic clinical internship year ( n = 2; Al-Hussami & Darawad, 2013; Xiong et al, 2017). One recruited students across program years (Hassan, 2018).…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation